Assessing composition and diversity of woody vegetation in mined arid and semi arid lands of Kerio valley, Kenya - Barsosio, Abraham; Kirui, Bernard; Maara, Nelson (International Journal of Biological Research, 2016)
The woody vegetation in semi-arid area is important in providing ecosystem services and goods. However, it faces threats manifested in land-use changes such as mining. This study aimed at assessing the composition and diversity of woody vegetation as well as inherent soil physico-chemical parameters in a previously mined area and comparing it with a semi-pristine adjacent area.Â  Six transects containing five plots each were established within two blocks separated by a river. In each plot, data was collected on woody tree growth characteristics and soil parameters. Thirteen woody species were recorded in the rehabilitated mined and twenty two in semi-pristine sites with Ficus sycomorus L Moraceae being the dominant species at the two sites. Woody vegetation diversity was higher in semi-pristine site than in the rehabilitated mined site. However, this was not significant (t-test, =D.F=1 P=0.767). Mean soil nutrients (F2, 7. = P=0.821), pH (F2, 7. =109.88, P=xxx), was higher in rehabilitated mined sites while mean soil temperature (F2, 7. =9.08, P=0.011) was higher in mined areas. Rehabilitating mined sites can bring back species diversity, composition, however what is not clear is whether ecosystem functions are restored.Â